RUJUK: PERUNTUKAN UNDANG-UNDANG DAN PELAKSANAANNYA DI MALAYSIA - Abdullah, Raihanah; Mahmod, Zulzaidi (Jurnal Syariah, 2010)
The problem of ruju‘ arises when it relates to the question of whether an act of intercourse between a husband and wife who are divorced within the period of ‘iddah is deemed as ruju‘ or otherwise. Several Syariah Court cases indicate that the court is certain as to the principles in the mazhab of Shafi’i that such an act is not deemed as ruju‘ unless ruju‘ has been uttered or pronounced prior to that act. Emphasis by the Syariah Court in the application of the principles of mazhab Shafi’i in matters pertaining to ruju‘ bi al-fi‘li has in some way caused problems in the community. As such this article reviews the situation of ruju‘ from the perspective of Islamic law and its implementation according to Islamic family laws in Malaysia.